El Evangelio de Elisa Victoria (2021) y el concepto de escritura femenina - Romero Polo, Paula (2025)
In this article, we analyze El Evangelio (2021) by Elisa Victoria in light of the question of women’s writing, with the aim of expanding the range of issues that are normally discussed applying this concept. Toril Moi (2008) suggested that women’s writing has become a marginal topic in gender studies due to theoretical issues. After reviewing different theoretical approaches to women’s writing, we claim that the partial abandonment of this notion and the rejection it provokes in some female writers and literary critics are actually due to a misuse of this concept by feminist criticism. Seeking to address this tendency, in the second part of the article we read El Evangelio as an example of women’s writing, focusing on the novel’s interest in depicting the everyday life of its protagonist.